Effectiveness of Nano-hydroxyapatite-coated Implants against Peri-implantitis Bacteria - Ibrahim Fazal; Vanshi Bangia; Ashutosh Yadav; Divya Batra; Sunil Kar; Sameer Gupta (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Peri-implantitis, a prevalent complication of dental implants, is characterized by inflammation and bone loss caused by bacterial colonization around the implant surface. Nano-hydroxyapatite (nHA)-coated implants have shown promise in enhancing osseointegration and providing antibacterial properties. Materials and Methods: A total of 40 dental implants were divided into two groups: Group A (n = 20) comprised nHA-coated implants, and Group B (n = 20) comprised uncoated titanium implants (control). The implants were incubated with Porphyromonas gingivalis, Fusobacterium nucleatum, and Aggregatibacter actinomycetemcomitans in vitro for 7 days. Antibacterial efficacy was assessed by quantifying colony-forming units (CFUs) using culture techniques. Additionally, biofilm formation on implant surfaces was evaluated using scanning electron microscopy (SEM). Results: Group A demonstrated a significant reduction in bacterial adhesion and biofilm formation compared to Group B (P < .05). The mean CFU counts for P. gingivalis, F. nucleatum, and A. actinomycetemcomitans in Group A were 1.2 × 104, 0.9 × 104, and 0.8 × 104, respectively, compared to 3.5 × 104, 2.8 × 104, and 2.4 × 104 in Group B. SEM analysis revealed a thinner biofilm layer on nHA-coated implants, indicating superior antibacterial activity. Conclusion: Nano-hydroxyapatite-coated implants significantly inhibit the growth of peri-implantitis-associated bacteria and reduce biofilm formation, making them a promising alternative for reducing peri-implantitis risk. Further clinical studies are warranted to validate these findings.